ANALISIS STRATEGI MANAJEMEN PERUBAHAN DALAM MENINGKATKAN EFEKTIVITAS PELAYANAN INFRASTRUKTUR DI DINAS PEKERJAAN UMUM DAN TATA RUANG KOTA GUNUNGSITOLI - Fince Cius Putra Zega; Palindungan Lahagu; Eliagus Telaumbanua; Meiman Hidayat Waruwu (Lembaga Pengembangan Kinerja Dosen, 2026)
Infrastructure development is one of the main indicators of a region’s overall development success. Adequate infrastructure plays a strategic role in enhancing regional connectivity, accelerating the distribution of goods and services, and expanding public access to essential facilities. Various efforts have been made by the local government to improve work systems and accelerate development; however, several challenges remain, such as inadequate planning, limited human resources, and suboptimal supervision effectiveness. Based on these conditions, this study aims to analyze the change management strategies implemented, identify the challenges encountered, and examine the efforts made to improve infrastructure services by the Department of Public Works and Spatial Planning (PUTR) of Gunungsitoli City. This research employs a qualitative descriptive method with data collection techniques including observation, in-depth interviews, and documentation. The research informants consist of leaders, structural officials, and community members who benefit from infrastructure services. The results indicate that the change management strategies implemented by the PUTR of Gunungsitoli City have shown positive progress, although not yet fully optimal. Constraints such as limited planning data, delays in material distribution, and gradual adaptation of employees to digital systems still occur. Improvement efforts are carried out through strengthening cross-sector coordination, utilizing data-based information systems, and continuous human resource development to ensure infrastructure services become more effective and well-targeted.